Efek Permainan Blok terhadap Perkembangan Motorik Halus pada Anak dengan Retardasi Mental: Studi Kasus - Gita Salsa Viera Fitriani; Dian Ramawati; Eni Rahmawati (Journal of Bionursing, 2022)
Mental retardation is a person who has limitations in intelligence that is below average, this affects self-care independently. Mentally retarded children are also said to be children who have limitations in terms of their intellectual mentality, because there are difficulties in communicating, doing academic tasks, and socializing. Motor development is the development of the body that produces movement. The fine motor development of mentally retarded children can be stimulated by playing blocks. The block game has characteristics such as having a variety of geometric shapes and each geometric shape in the block game is painted in colorful colors. This study aimed to evaluate the effectiveness of block playing on fine motor development in children with mental retardation. The method used is a case study, pretest and posttest comprising of 4 respondents. The instrument utilized in this examination is the after effect of variation. Results from bivariate analysis using the paired sample t-test indicated the average difference between the pre-test and post-test which shows the p-value = 0.022, so there was a difference between the pre-test (before the intervention) and post test (after the intervention). It concluded that there was an effect of playing blocks on fine motor development in mentally retarded children.